Life after eruption VIII: The orbital periods of novae. Issue 4 (10th November 2020) - Fuentes-Morales, I; Tappert, C; Zorotovic, M; Vogt, N; Puebla, E C; Schreiber, M R; Ederoclite, A; Schmidtobreick, L
ABSTRACT: The impact of nova eruptions on the long-term evolution of Cataclysmic Variables (CVs) is one of the least understood and intensively discussed topics in the field. A crucial ingredient to improve with this would be to establish a large sample of post-novae with known properties, starting with the most easily accessible one, the orbital period. Here we report new orbital periods for six faint novae: X Cir (3.71 h), IL Nor (1.62 h), DY Pup (3.35 h), V363 Sgr (3.03 h), V2572 Sgr (3.75 h), and CQ Vel (2.7 h). We furthermore revise the periods for the old novae OY Ara, RS Car, V365 Car, V849 Oph, V728 Sco, WY Sge, XX Tau, and RW UMi. Using these new data and critically reviewing the trustworthiness of reported orbital periods of old novae in the literature, we establish an updated period distribution. We employ a binary-star evolution code to calculate a theoretical period distribution using both an empirical and the classical prescription for consequential angular momentum loss. In comparison with the observational data we find that both models especially fail to reproduce the peak in the 3–4 h range, suggesting that the angular momentum loss for CVs above the period gap is not totally understood.